Manufactured Cell Blocks: Turning Smears into Sections - Kang, A.; Miranda, Alina; De Boer, B. (2018)
© 2019 S. Karger AG, Basel. Whilst cytological smears are still the basis of cytodiagnosis, there is an increasing role for ancillary testing. Specimens obtained are not always optimal, often with limited material for ancillary studies. Several reports have described the utility of scraping material from cytological smears to manufacture cell blocks to provide material for ancillary studies. Our objective was a retrospective review of the PathWest (QE2) experience with manufactured cell blocks (mCB) over the last 10 years. A total of 178 fine-needle aspiration cases with mCB were extracted from the PathWest database. Data were subdivided into: lymph node (89), breast (31), thyroid (23), soft tissue (13), liver (11), and other sites (11) and were analysed. All available material was reviewed. Diagnostic material was identified in 163 mCB (91.6%). Immunohistochemistry (IHC) was performed on 149 cases. Positive IHC staining was seen in 139 cases (93.3%) and advanced the diagnosis in 119 cases (79.9%). Molecular studies were performed on 38 mCB with adequate DNA obtained in 37 cases (97.3%). Our review has demonstrated that cellular material scraped from air-dried or prefixed smears can be made into cell blocks. Antigen preservation is adequate to provide diagnostically useful results with IHC whilst DNA integrity is preserved to allow molecular analysis.